2020
DOI: 10.1136/bmjopen-2020-038927
|View full text |Cite
|
Sign up to set email alerts
|

Towards a multilevel governance framework on the implementation of patient rights in health facilities: a protocol for a systematic scoping review

Abstract: IntroductionPatient rights are “those rights that are attributed to a person seeking healthcare”. Patient rights have implications for quality of healthcare and acts as a key accountability tool. It can galvanise structural improvements in the health system and reinforces ethical healthcare. States are duty bound to respect, protect and promote patient rights. The rhetoric on patient rights is burgeoning across the globe. With changing modes of governance arrangements, a number of state and non-state actors an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 34 publications
0
18
0
2
Order By: Relevance
“…rules in practice to implement patient rights). Our initial conceptual framework (Putturaj et al, 2020) is grounded in the literature on patient rights, public policy implementation and multilevel governance to guide the evidence synthesis on grievance redressal. This initial framework was refined based on the review we undertook, as described below.…”
Section: Theoretical Lens Appliedmentioning
confidence: 99%
See 2 more Smart Citations
“…rules in practice to implement patient rights). Our initial conceptual framework (Putturaj et al, 2020) is grounded in the literature on patient rights, public policy implementation and multilevel governance to guide the evidence synthesis on grievance redressal. This initial framework was refined based on the review we undertook, as described below.…”
Section: Theoretical Lens Appliedmentioning
confidence: 99%
“…We used NVivo V.12 software for coding the data. To iterate between the previously published theoretical framework (Putturaj et al, 2020) and the data emerging from the review, we adopted both inductive and deductive approaches. The authors discussed and resolved any discordant views on data collection and analysis.…”
Section: Search Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…In light of the need of patients to be aware of their rights, health institutes must learn about information-seeking behavior and possible information channels and how to convey patient rights effectively. Furthermore, research on patient rights is relatively scant [15,16]. The juxtaposition of patients' awareness of their rights with credibility as a main construct and limited health communication research accentuates the importance of the current study.…”
Section: Introductionmentioning
confidence: 98%
“…3–5 In this regard, several countries have developed institutional arrangements intended to receive, examine and resolve the complaints raised by individuals about their healthcare encounters. 6 Care-seeking individuals can raise grievances concerning technical aspects of care (eg, clinical care provided) or non-technical aspects of care (eg, staff-patient relationships and management-related issues). Few qualitative studies found that exorbitant costs, lack of time to raise and follow-up the complaints, lack of or inadequate practical and emotional support to pursue complaints, inadequate financial resources deter care-seeking individuals from availing grievance redressal services.…”
Section: Introductionmentioning
confidence: 99%